2017
DOI: 10.19082/5863
|View full text |Cite
|
Sign up to set email alerts
|

Self-care behavior of type 2 diabetes mellitus patients in Bandar Abbas in 2015

Abstract: BackgroundDiabetes self-care helps to control the blood sugar which, in turn, results in a better state of health. However, more than 50% of diabetic patients do not have self-care capabilities.ObjectiveTo determine type 2 diabetes self-care capabilities among patients visiting a Bandar Abbas diabetes clinic in 2016.MethodsThe present descriptive-analytical research was of a cross-sectional type. The sample was comprised of 120 patients afflicted with type 2 diabetes, who had been selected through the simple r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…Among the barriers of regular medication busy schedule, forgetfulness and diabetes-related distress for regular medications showed a positive correlation with high HbA1c. In addition, regular monitoring of blood glucose may be the motivational factor and encourage self-management of diabetes 30,44. There was a significant relationship between regular monitoring of blood sugar with good glycaemic control in our study.…”
Section: Discussionsupporting
confidence: 49%
“…Among the barriers of regular medication busy schedule, forgetfulness and diabetes-related distress for regular medications showed a positive correlation with high HbA1c. In addition, regular monitoring of blood glucose may be the motivational factor and encourage self-management of diabetes 30,44. There was a significant relationship between regular monitoring of blood sugar with good glycaemic control in our study.…”
Section: Discussionsupporting
confidence: 49%
“…In Mahmoudi's (2006) survey, 60 Type 2 diabetic patients were educated about self-care behaviors for three months and results manifested a significant correlation between self-care behaviors and quality of life and overall health status. In Karimi et al (2017) study, it was revealed that nearly 70% of the self-care capability of diabetic patients was poor and self-care behaviors were defined as one of the important and appropriate factors involved in the better health status.…”
Section: Quality Of Life In Diabetic Patientsmentioning
confidence: 99%
“…Self-care behaviors such as monitoring blood glucose, medication and foot care are other important factors that influence the quality of life and treatment costs in diabetic patients (Kim and Han, 2020). Thus, learning skills to cope with self-care management is necessary for optimal control of diabetes (Karimi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Praktik self care sebaiknya dikembangkan dan diintegrasikan dalam diabetes self care education (Raithatha, 2014). Perilaku self care memiliki peran penting untuk pencegahan komplikasi jangka pendek dan jangka panjang sehingga sangat diperlukan program edukasi agar pengobatan DM dapat berjalan dengan baik (Karimi, 2017). Metode Edukasi yang baik dan terintegrasikan secara tepat akan mempengaruhi perilaku self care dan kadar gula darah (Zandinava, 2017).…”
Section: Latar Belakangunclassified